Fair Assessment pada Kolaborasi Pemodelan Persyaratan Perangkat Lunak UML - Danang Wahyu Utomo; Egia Rosi Subhiyakto; Defri Kurniawan (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
In software engineering education, students are expected to be able to collaborate with other student in team project. Based on the RPS and Software Engineering syllabus, student must be able to create SRS document in group assignment. In general, lecturers assess students based on team cohesiveness, student accuracy in answering questions, and final result of SRS documents. The weakness of the assessment model is that the lecturer cannot know student who are really active and contribute to the team. Student will get the same marks. There is no difference in marks between active and passive students. The impact, active student can become passive, because the result obtained in the presentation of final assignment is no different from the other student. It can make student contribution decrease. Student are reluctant to group in completing their final assignments. This paper aims to propose a fair assessment approach to provide an assessment that is appropriate to the composition of group assignment. Fair assessment consists of assignment component, diagram modeling, and final project. In addition, re-implementation was carried out on the previous collaborative tool by replacing the assessment model and adding some features such as friend search menu and real time discussion. The evaluation involved 55 students majority in Software Engineering to test fair assessment approach and new features of collaboration tool. The result shows that students agree that a fair assessment approach is appropriate to be used in supporting collaborative software engineering education, especially UML diagram modeling.